Body composition in elite sprint runners - Skorocka, I.; Bunc, V. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction The monitoring of the body composition changes, particularly of body mass, percentage of body fat and lean body mass, has become a frequent component of not only clinical assessment of health condition, but also of training practice. It can help to diagnose overtraining (Roche et al. 1996) or incomplete coping of athletes with the training load. Disorders in body water can indicate many illness. The segmental fluid distribution may signalize assymetry in body composition or can help to diagnose injuries. The purpose of this study was to determine characteristic traits of body composition of elite runners and to rmonitor long-term changes of body composition of a selected subgroup over two years. Subjects and Methods This study was carried out on 28 subjects, 11 female and 16 male members of Czech national teams - 400 m and 400 m hurdles ( males: mean age ±S.D. was 22.4± 3.41 years, body mass 73.67±4.48 kg, body height 183.3±5.16 cm, females: mean age 18.6±2.77 years, body mass 58.45±3.62kg, body height 173.3±3.62 cm). We estimate the total body water (TBW) divided into intracellular (ICW) and extracellular water (ECW), ratio of extracellular cell mass to intracellular cell mass (ECM/BCM), body fat, lean body mass (LBM) derived from whole-body bioimpedance measurement at different frequencies - 1, 5, 50 and 100 kHz (B.I.A. 2000M, Data Input, Germany). Segmental fluid distribution into extremities and trunk was measured using bioelectrical impedance analysis InBody 3.0 at frequencies 5, 50, 250 a 500 kHz (Biospace Co., Ltd., Seoul, Korea). In the subjects we observed dominant arm and reflective leg. In the subgroup of 13 athletes we measured the body composition regularly in the preparatory and the competitive period of the training over two years. Results The results of fluid distribution ICW and ECW show, in percentage expression, non-signifikant differences between men and women in this group of athletes (males: mean TBW 48.44±3.6 l, ICW 28.40±2.34 l, ECW 20.04±1.42 l, females: mean TBW 33.81±1.37 l, ICW 19.28±0.86 l, ECW 14.53±0.64 l). The results of segmental bioelectrical impedance analysis indicate symmetrical placement of fluid in lower and upper extremities by men and women. In men the percentages of body water in component segments were 47.3±7.4% trunk, 35.0±4.8% lower extremities and 12.5±2.9% upper extremities. In women these were 47.6±4.1% trunk, 37.3±2.5% lower extremities and 10.6±1.9% upper extremities. As a result of the two-year monitoring of body composition in the subgroup of 13 runners we can see fluctuations in average body weight of ± 2.4 kg, percentage of body fat ± 0.80 % and TBW aprx. ±2.24 l. These changes are not significantly different (p<0.01). The lowest values of ECM/BCM were measured in the competitive period in the time when intensity over the volume in the training predominates. The changes of ECM/BCM in the preparatory and competitive periods are significantly different (p<0.01) and are not accompanied by characteristic changes of body fat. Discussion/Conclusion The same proportional representation of ICW a ECW in men and women - sprint runners - is probably a result of the relatively same content of the sport preparation in the sense of the volume: intensity ratio. In this group of athletes the fluid distribution in extremities was symetrical with the dominance of the right upper extremity and right lower extremity used in the jump. Laterality did not show in the volume of fluids in body segments. The laterality may appear rather in qualitative parameters of the muscle, e.g. in neuromuscular coordination, than quantitativ description of the muscle. From the point of view of long-term body composition monitoring, the character of the sports preparation, while retaining relatively stable values of the body weight and percentage of body fat, will show in the ECM/BCM. This parameter appears to be, in accordance with our results, as an important indicator of the level of the fitness achieved by training in sports preparation.